Improving the critical thinking ability of class 5 students in science learning using the project based learning model - Silvia, Okeu Wila; Jayadinata, Asep Kurnia; Rahayu, Galih Dani Septiyan (Sekolah Pascasarjana UPI, 2024)
This research is motivated by the problem of low critical thinking skills of class V students at SDN Wahir in science learning. Science learning encourages students to think at a higher level, analyze, design and create a product/work. Therefore it takes high-level thinking skills to achieve good science learning. This study aims to describe the Project Based Learning (PJBL) model that is implemented to overcome the problem of students' low critical thinking skills. This research is a qualitative research using classroom action research methods. Data were collected by observation, interviews, documentation and data acquisition were analyzed descriptively qualitatively. Researchers analyzed the data by means of data reduction, data presentation, and drawing conclusions and verification. This research was conducted in two cycles while the percentage of the first cycle was based on the implementation of learning with the results of students' critical thinking skills of 62.50% achieving the target of success indicators for critical thinking skills, and 68.75% of students' learning outcomes reaching the target exceeding the KKM. In cycle II there was an increase in students' critical thinking skills of 81.25% reaching the target with learning outcomes of 87.50% reaching the target above the KKM. The data shows that students' critical thinking skills in science learning have increased through the application of the Project Based Learning (PJBL) model.